Explaining the UK's 'high-risk' approach to type 2 diabetes prevention: findings from a qualitative interview study with policy-makers in England - Barry, E; Greenhalgh, T; Papoutsi, C; Shaw, S (BMJ Publishing Group, 2023)
Objectives When seeking to prevent type 2 diabetes, a balance must be struck between individual approaches (focusing on people’s behaviour ‘choices’) and population approaches (focusing on the environment in which those choices are made) to address the socioeconomic complexity of diabetes development. We sought to explore how this balance is negotiated in the accounts of policy-makers developing and enacting diabetes prevention policy.